Knowledge of Dentists and Dental Undergraduates Related to COVID-19 - Giselle Emilãine da Silva Reis; Maria Fernanda Pivetta Petinati; Katheleen Miranda dos Santos; Jennifer Tsi Gerberb; Tatiana Miranda Deliberador; Juliana Feltrin de Souza; Nelson Luis Barbosa Rebellato; Rafaela Scariot (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the knowledge of Brazilian dentists and final-year dental undergraduates concerning COVID-19. Material and Methods: We conducted a self-administered online questionnaire about the symptoms, incubation period, and transmission routes of COVID-19. In total, there were three questions addressing these topics and 15 correct answers, so each participant could score from 0 to 15 points. Besides that, data such as sex, age, education level, years of work experience and place of work were collected. All data were submitted to statistical analysis with a 5% significance level. Results: 476 participants were recruited. Regarding the respondents' perception of the most common symptoms of COVID-19, 99.4% responded fever, 95.2% cough, and 99.2% dyspnea. About the incubation period, 56.3% answered from 1 to 14 days. About the transmission routes, 98.3% recognized transmission through droplets, 80.3% through direct contact with infected persons, and 70.4% through indirect routes. The median knowledge score was 10 (4 - 14). Regarding the socio-demographic variables, participants aged 30 years or more had a higher score than those aged up to 29 years old (p=0.004). For education level, specialist dentists presented a higher score than undergraduates (p=0.006), general dentists (p=0.048) and Ph.D. (p=0.016). Participants with 15 years or more of work experience had a higher score than undergraduates (p=0.003). Concerning the workplace, participants working in the public sector had a higher score than those working in the private sector or universities (p=0.015). Conclusion: Participants recognized the main symptoms, incubation period, and transmission routes of the COVID-19 virus; however, the knowledge level of specialist dentists, older dentists, more experienced dentists, and dentists working in the public sector was higher than the other participants.